2016
DOI: 10.17583/remie.2016.1697
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Academic Achievement Risk Assessment Scale for Undergraduates: Low, Medium and High Achievers

Abstract: This research has developed The Academic Achievement Risk Assessment Scale [AARS], for identification of the factors which influence performance of undergraduate (448 students); studying at three universities of Lahore, Pakistan. An 18-item scale, with five distinct factors was developed which included lack of motivation, dysfunctional parental practices, parental involvement in drug abuse or antisocial activities, difficulty with peers, and language barrier. The results revealed differences among low, medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Considering the global needs, many non-English speaking countries also include English as a subject in their education programme [18,19]. Today, not only medicine but also many other undergraduate courses in Sri Lankan universities are taught only in English and, thus, students have no choice but to follow the course in English.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the global needs, many non-English speaking countries also include English as a subject in their education programme [18,19]. Today, not only medicine but also many other undergraduate courses in Sri Lankan universities are taught only in English and, thus, students have no choice but to follow the course in English.…”
Section: Open Accessmentioning
confidence: 99%
“…These studies identified the language barrier as a negatively influencing factor for both study performances and social well-being of international students [17,18]. Moreover, even in home countries, language is known to restrict high achievements when the teaching-learning activities are conducted in English or a language different from their first language [19]. It is also identified as a factor that negatively affects effective communication [20]; one of the essential skills that should be developed in undergraduates.…”
Section: Introductionmentioning
confidence: 99%